Management of pancreatic walled-off necrosis using an ultrasonic pneumatic lithotripsy system and double-catheter aspirated lavage performed through drainage tract: a case report. Issue 3 (March 2022) - Lu, Bei; Yin, Junjie; Wang, Jingrui; Cai, Yang; Xu, Xiao
Patients with pancreatic walled-off necrosis (WON) treated by minimally invasive approaches often require repeated necrosectomy instead of conventional open necrosectomy. A 55-year-old woman with lateral infected pancreatic WON was successfully treated by an infrequently used technique involving an ultrasonic pneumatic lithotripsy system (UPLS) and double-catheter aspirated lavage through a percutaneous drainage tract. No perioperative complications occurred. The mean operating time of the repeated procedures was 35 minutes (range, 25–48 minutes). The total hospitalization stay was 46 days, and no recurrence of the fluid collection was observed during the 15-month follow-up period. UPLS-assisted necrosectomy and double-catheter aspirated lavage is an alternative technique for lateral WON that fails to improve by percutaneous drainage. It efficiently combines disintegration and aspiration procedures and can be safely repeated under total intravenous anesthesia through sinus tracts.